A Family of Bi-Univalent Functions Defined by( p, q)-Derivative Operator Subordinate to a GeneralizedBivariate Fibonacci Polynomials (European Journal of Pure and Applied Mathematics, 2024)
Making use of a generalized bivariate Fibonacci polynomials, we propose a family of normalized regular functions ψ(ζ) = ζ + d2ζ2 + d3ζ3 + · · · , which are bi-univalent in the disc {ζ ∈ C : |ζ| < 1} involving (p, q)-derivative operator. We find estimates on the coefficients |d2|, |d3| and the Fekete-Szeg¨o inequality for members of this family. New implications of the primary result as well as pertinent links to previously published findings are also provided.